In Situ Vaccination of Tumors Using Plant Viral Nanoparticles - Murray, Abner A. (Methods Mol Biol, 2019)
Viral nanoparticles are self-assembling units that are being developed and applied for a variety of applications. While most clinical uses involve animal viruses, a plant-derived virus, cowpea mosaic virus (CPMV) has been shown to have antitumor properties in mice when applied as in situ vaccine. Here we describe the production and characterization of CPMVand its use as in situ vaccines in the context of cancer. Subsequent analyses to obtain efficacy or mechanistic data are also detailed.